2020
DOI: 10.13189/ujer.2020.081019
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Online Learning during the Covid-19 Epidemic in Indonesia: Assessment of Higher Education Students' Use and Implementation of Online Learning Technology

Abstract: By the end of 2019, the Covid-19 virus was causing concern around the world. It quickly claimed Indonesian government attention-especially as the government was already anticipating a spread of online education technology around the world that was already underway. The Indonesian Ministry of Education and Culture appealed to educators for help in the creation of online programs. Researchers have tried to assess the ability of Indonesian tertiary level students to adapt to and implement online education technol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 2 publications
(2 reference statements)
0
13
1
5
Order By: Relevance
“…Another assumption is that home wifi may be a better choice for a better internet package plan if online learning were to persist in the succeeding semesters. While Dian Hidayati et al (2020) [24] data too found that limited internet coverage in certain geographical locations to contribute the most to online learning discomfort experienced by the respondents in Indonesia, this study found that in some cases remote geographical locations could be accessed by more expensive high-speed internet coverage plan. Hence, the main hurdle remains the socio-economic income of the family.…”
Section: The Contribution Of Family Socio Economic Background On Onlicontrasting
confidence: 63%
“…Another assumption is that home wifi may be a better choice for a better internet package plan if online learning were to persist in the succeeding semesters. While Dian Hidayati et al (2020) [24] data too found that limited internet coverage in certain geographical locations to contribute the most to online learning discomfort experienced by the respondents in Indonesia, this study found that in some cases remote geographical locations could be accessed by more expensive high-speed internet coverage plan. Hence, the main hurdle remains the socio-economic income of the family.…”
Section: The Contribution Of Family Socio Economic Background On Onlicontrasting
confidence: 63%
“…The condition of some teachers does not understand about internet technology or the use of various online learning media, especially those in the regions. The results in less efficient learning, lack of student concentration and difficulty in understanding, asking and answering questions and discussing the material learned during online learning [6]. The need for teachers in facing online learning has led governments, universities, and other institutions to create training courses that held online.…”
Section: Introductionmentioning
confidence: 99%
“…The rapid development of information technology has shown that online learning has become an actual trend in education [43]. The online learning method eases people to access the course contents [44] and removes time and distance barriers [45]. Moreover, online learning continues to increase as a means of learning and improves the quality of education.…”
Section: Online Learningmentioning
confidence: 99%
“…This highly-dependent-on-technology method is very supportive in carrying out teaching and learning activities for students as well as in putting them in collaborated learning [47]. Online learning is similar to several identical learning methods such as e-learning, internet learning, web-based learning, teleconference, and distributed learning [48]. Online learning frequently applies the e-learning model and it has proven significantly to give a positive effect on the students' academic achievement [49], [50].…”
Section: Online Learningmentioning
confidence: 99%